The Colorado golf carbon project - Gillette, Katrina, author; Qian, Yaling, advisor; Follett, Ronald F., committee member; Delgrosso, Steven J., committee member; Koski, Anthony, committee member; Conant, Rich, committee member (Colorado State University. Libraries, 2014)
There is concern regarding the rise of greenhouse gas (GHG) emissions and the impending effects of global climate change. Soils are the largest pool of C on earth with small changes having potentially significant effects on atmospheric carbon dioxide (CO2) concentrations. Soil emits a substantial portion of nitrous oxide (N2O), and is an important sink for balancing atmospheric methane (CH4) through microbial oxidation. Anthropogenic management of soil is therefore critical in mitigating the effect of climate change by increasing biological sinks and reducing GHG emissions. Due to recent rapid urban expansion and the common use of turfgrass as ground cover and its associated management, these areas are becoming increasingly important for regional accounting of GHG budgets. Golf courses in particular are important economical green spaces that are intensively managed with common practices that include frequent irrigation, mowing and fertilization. Such management practices increase biogeochemical cycling of C and N fine quality turfgrass system and may therefore help mitigate atmospheric CO2 through increase soil organic carbon (SOC) sequestration. However, intensive management of turfgrass may also increase emissions of N2O and reduce CH4 oxidation potentials, and therefore it is critical to have a complete account of GHG fluxes in the system. The objective of this dissertation was to estimate the carbon balance of golf courses using a multifaceted approach that included survey data, ecosystem modelling of C and N dynamics in turfgrass, and a two year field study measuring trace gas fluxes from a golf course using different urea fertilizers. Survey information was collected from Colorado golf courses regarding energy use from clubhouses, management facilities, and fertilizer and irrigation management, and land use. Further calculations were made from published literature for fertilizer production, N2O emissions and C offsets through SOC sequestration in regards to land use type. Survey information was also used to evaluate the effects of different management scenarios reported by turfgrass managers in order to simulate SOC accumulation and N2O fluxes using the DAYCENT biogeochemical model on a near (25 yr) and long (50 yr) term time scale. Finally, soil GHG fluxes were monitored using a modified version of the closed chamber method over the course of a two year field study, where the effects of fertilizer treatment, turfgrass site, and soil drainage potential were evaluated. Soil organic C and N were also measured for future analysis from all field plots. Through these efforts we have encompassed critical components required to calculate an overall C balance of golf course facilities maintained in the state of Colorado. Energy consumption from clubhouse and maintenance facilities and irrigation pumping stations were the largest sources of emissions, therefore increasing energy efficiency may significantly reduce annual emissions from golf courses. Of the twenty-two golf courses around the state of Colorado that participated in the survey, most had similar areas of managed turfgrass and nearly all maintained alternative land use types apart from turfgrass. Increasing the area of natural grassland and trees that have minimal management inputs is important to offset the C intensive management required to maintain the aesthetics of fine quality turfgrass. Alternative land use types contributed to C offsets through SOC accumulation not only for turf management, but offset approximately 40% of CO2 emissions from building and irrigation systems. In our second analysis we used the DAYCENT model to make projections of SOC and N2O emission over several periods of time; simulations were based on fertilizer rates reported in the survey to evaluate different management scenarios. The model projected rapid SOC sequestration rates when turfgrass was newly established, but these rates decreased and N2O emissions substantially increased after 25 yr if best management practices were not used. Field trials were the third and final part of our study, and we observed greater N2O emissions from fairways than from the rough turfgrass sections for all fertilizer treatments; a likely result of taller mowing height that increased plant water transpiration as well as from an increased layer of thatch on the Kentucky Bluegrass rough that partially immobilized N applications. Of the fertilizer treatments, Polyon with advanced coated technology was the most effective in restricting N substrate to control N2O emissions, especially following summer fertilizer applications. Using fertilizer technologies that reduce the risk of loss is important both economically and environmentally. Soil water and temperature were important abiotic variables affecting N2O and CH4 emissions, with emissions increasing as high soil water content depleted soil oxygen and rising summer temperatures reduced C3 turfgrass physiological activity. Observations collected in the field signify important GHG mitigation strategies in managing turf irrigation and fertilizer, as well as effective fertilizer technologies to reduce N2O emissions. If turfgrass managers are to employ the best GHG mitigation strategies to fine quality turf, there must be a complete understanding of the variables effecting soil GHG emissions that include N substrate availability, soil water and temperature, and plant physiology.
Keywords: carbon dioxide; turfgrass; green house gas emissions; golf course